Cleavage-embryo genes and transposable elements are regulated by histone variant H2A.X - Kai-yi SUN; Shi-meng GUO; Gui-ping CHENG; Ying YIN; Ximiao HE; Li-quan ZHOU (The Society for Reproduction and Development, 2021)
During mammalian preimplantation development, stimulation of zygotic genome activation (ZGA) and transposable elements (TEs) shapes totipotency profiling. A rare mouse embryonic stem cells (mESCs) subpopulation is capable of transiently entering a state resembling 2-cell stage embryos, with subtypes of TEs expressed and ZGA genes transiently activated. In this study, we found that deletion of H2A.X in mESCs led to a significant upregulation of ZGA genes and misregulated TEs. ChIP-seq analysis indicated a direct association of H2A.X at the Dux locus for silencing the Dux gene and its downstream ZGA genes in mESCs. We also demonstrated that histone variant H2A.X is highly enriched in human cleavage embryos when ZGA genes and TEs are active. Therefore, we propose that H2A.X plays an important role in regulating ZGA genes and TEs to establish totipotency.